Socio-economic status of fishers in Allaipiddy village, Jaffna - Ragavan, N.; Sivashanthini, K.; Sutharshiny, S. (University of Jaffna, 2016)
The present study was carried out in Allaipiddy for a period of eight months from June 2014 to January 2015. The socio-economic data of randomly selected 53 fishermen was obtained through pre-tested structured questionnaire, in-depth guided interview and observation. Descriptive analysis of the direct social demography was done by using SPSS. All fishermen are Catholics and Sri Lankan Tamils. The sex demography of the community explicit that male is higher in percentage (54.4 %). In the fisherfolk, families with five members are higher in percentage (33 %) and most of them are nuclear families (95 %). Majority of the active fishermen fall in the 36 – 45 age-group. All the fishermen are having primary education and only 21 % of them are teetotalers. The existing fishing methods are underwater-Sirahuvalai (46 %), Seer-net fishing (21 %), Driftnet fishing (13 %), Crab-net fishing (11 %) and Arakodiyan-net fishing (9 %). Majority of fishers (90 %) are earning Rs. 20,000 to Rs. 40,000 per month, while 6 % of them earn as high as Rs. 40,000 to Rs. 60, 000. The economic analysis of the Allaipiddy fisherfolk reveals that high income earning fishermen are involved in underwater-Sirahuvalai.
Keywords: Education; Fishers; Income level; Questionnaire; Socio-economic